PENINGKATAN KETERAMPILAN BERHITUNG PESERTA DIDIK DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD MELALUI PAPAN JURANG - Endang Ratih; Sumianto; Putri Hana Pebriana; Iis Aprinawati; Yenni Fitra Surya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the low math counting skills of class II students totaling 24 people, 14 male students and 10 female students. This study aims to improve the counting skills of grade II elementary school students through the use of the STAD type cooperative learning model with the help of ravine board props, in learning mathematics. This research is a class action research (PTK) conducted in two cycles at UPT SDN 007 Bangkinang. Data collection techniques in this study used documentation techniques, observation techniques, and test techniques. The instruments in this study used learning tools such as ATP, teaching modules, and student worksheets (LKPD). The data analysis technique in this study uses qualitative data, and quantitative data. Based on data analysis, it can be seen that there is an increase in students' counting skills. Before the action, the completeness of the results of students' counting skills was only 33% with a very poor category. In carrying out cycle I meeting I, the completeness of the results of students' counting skills reached 60.56% with the category less. In cycle I meeting 2, the test results of students' counting skills reached 72.66% in the sufficient category. Whereas in cycle 2 meeting I, the test results of students' counting skills reached 76.60% still in the sufficient category. In cycle 2 meeting 2, the test results of students' counting skills reached 85.35% in the good category. This it can be concluded that students' counting skills can be improved by using the STAD type cooperative model using the ravine board props.